CHARACTERISTICS OF USING MULTIMEDIA TECHNOLOGIES IN TEACHING ENGEENERING SCIENCES - Karimov Boxodir Yusufjonovich; Isroilov Nizomjon Nozimjon o’gli (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
The article presents concepts for teaching mechanical engineering using multimedia technologies in accordance with general methods and forms of teaching, designed to awaken in students a holistic vision of production and mechanical engineering.